Electrocatalytic reduction of CO2 on size-selected nanoclusters of first-row transition metal nanoclusters: a comprehensive mechanistic investigation. Issue 16 (12th April 2023) - Raju, Rajesh Kumar; Rodriguez, Paramaconi; Brothers, Edward N.
Abstract : Electrochemical reduction of CO2 to various fuel molecules on first-row transition metal nanoclusters. Abstract : Recycling CO2 back to fuels offers an ideal solution to control anthropogenic global CO2 emissions as well as providing a sustainable green solution to alternative energy resources from a cheap and earth-abundant carbon source. Size-selected nanoclusters open a novel area in catalysis as these atomically precise nanoclusters possess unique electronic and catalytic properties different from larger nanoparticles and traditional bulk catalysts. In this work, we have investigated the ability of first-row transition metal nanoclusters (Sc–Cu) of varying sizes (3 to 10 atoms) for CO2 electroreduction (CO2 RR). Employing computational hydrogen model (CHE), we have performed detailed analyzes on various CO2 RR electrocatalytic reaction pathways on all nanocluster surfaces. We have identified a general trend of decreasing adsorption energies while moving across the periodic table from Sc to Cu. Moreover, we have found a general preference for CHO* mediated pathways over COH* mediated pathways for methane formation. The CHO* mediated pathways prefer the reaction route via CHO* → CH2 O* → CH2 OH* → CH2 * → CH3 * → CH4 + * on most of the nanocluster surfaces. In addition, we have established that methanol formation is greatly disfavored on all nanocluster surfaces, and the release of CO and HCOOH is greatly suppressed on all nanoclusters. We have identified several nanoclusters as potential nanocluster-based electrocatalysts for CO2 RR for methane formation with relatively lower limiting potential values below 0.50 V. CO2 electroreduction versus hydrogen evolution reaction (HER) competition was also evaluated on various nanoclusters, and we identified a number of nanoclusters (Ti6, V5, V6, Mn4, Mn7, Mn10, Fe4, Fe8, Fe10, Ni4, and Cu5 ) that can suppress the formation of HER over CO2 RR. We have also established a linear scaling relationship between the adsorption free energies of various CO2 RR adsorbates to the adsorption free energies of CO2 *, O*, and C* adsorbates. We have found that scaling free energy relationships that exit on heterogeneous catalysts such as the correlation between the adsorption energies of AH x with the adsorption energies of atom A (A = C, N, O, S, etc. ) often breaks on nanocluster surfaces, especially for adsorbates with more than one binding motifs.